EXAMINING THE KNOWLEDGE OF FUTURE SPORTS PROFESSIONALS IN CONNECTION WITH WATER RESCUE AND LIFE-SAVING - Bihari, Dávid Tamás; Biró, Melinda (Stadium - Hungarian Journal of Sport Sciences, 2019)
Water drowning is a problem affecting the total population of the Earth. Drowning is a leading cause of death (one of every three deaths). On the planet, a man, a woman or a child drops into the water every two minutes. Every year, 4 million people worldwide are in danger of drowning, either in freshwater lakes or in the sea. Almost 10% of them do not survive the dive, so they die as a result of suffocation. More than half of those drowned in water are children or juveniles. Sports professionals, especially PE teachers, have a prominent role in preventing water accidents, so it is essential to be aware of life-saving and water-saving. The question arises as to what kind of knowledge these experts have on the subject and how they could stand up if it were wrong. The purpose of our research is to reveal the knowledge gaps and fears of students that prevent them from starting a rescue process. In our survey, we chose the questionnaire method, 147 students with PE or sports major participated. The results showed that a significant proportion, 64% of the students did not even see the resuscitation process. Most of them, 90%, did not resume the resuscitation experiment, 88% of them had not yet helped resuscitation. Most of them have no rescue practice, and their knowledge is incomplete for rescue and first aid.